2019
DOI: 10.1177/1352458519894713
|View full text |Cite
|
Sign up to set email alerts
|

High-dose biotin in progressive multiple sclerosis: A prospective study of 178 patients in routine clinical practice

Abstract: Background: A recent controlled trial suggested that high-dose biotin supplementation reverses disability progression in patients with progressive multiple sclerosis. Objective: To analyze the impact of high-dose biotin in routine clinical practice on disability progression at 12 months. Methods: Progressive multiple sclerosis patients who started high-dose biotin at Nantes or Rennes Hospital between 3 June 2015 and 15 September 2017 were included in this prospective study. Disability outcome measures, patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 24 publications
1
10
0
Order By: Relevance
“…Although the subgroup of patients with primary progressive MS was small and no statistically significant conclusions could be drawn from this cohort, biotin seems to have been used more frequently among these patients, since these were the study groups in clinical biotin trials. 69 An information guide on the use of vitamin D and biotin with evidence in favour of and against their supplementation is provided in Box 1.
Information guide on the use of vitamin D and biotin in multiple sclerosis.
…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Although the subgroup of patients with primary progressive MS was small and no statistically significant conclusions could be drawn from this cohort, biotin seems to have been used more frequently among these patients, since these were the study groups in clinical biotin trials. 69 An information guide on the use of vitamin D and biotin with evidence in favour of and against their supplementation is provided in Box 1.
Information guide on the use of vitamin D and biotin in multiple sclerosis.
…”
Section: Discussionmentioning
confidence: 99%
“… 6 A subsequent placebo-controlled study with 154 patients showed sustained reversal of MS-related disability in a subset of patients with progressive MS upon intake of 300 mg biotin per day. 7 On the other hand, two prospective studies reported no benefit of high-dose biotin on disability in progressive MS. 8 , 9 Failure to meet primary and secondary endpoints was also preliminarily reported from a large Phase III trial in progressive MS (NCT02936037). 10…”
Section: Introductionmentioning
confidence: 93%
See 2 more Smart Citations
“…Couloume and colleagues 1 have provided further evidence that very high doses of biotin do not improve the vast majority of individuals with progressive multiple sclerosis in a large cohort. These findings support those of a previous study of 43 individuals with the disorder who, for the most part, also did not improve on enormous doses of biotin.…”
mentioning
confidence: 98%